Influence of milking method, disinfection and herd management practices on bulk tank milk somatic cell counts in tropical dairy herds in Colombia. (February 2017) - Reyes, J.; Sanchez, J.; Stryhn, H.; Ortiz, T.; Olivera, M.; Keefe, G.P.
Highlights: Factors affecting bulk tank milk somatic cell count (BTSCC) in tropical dairy herds in Colombia were determined. The effects of milking method, disinfection and husbandry on BTSCC were examined. Hand-milking was associated with increased BTSCC, with a significant effect of month. Singeing udders and pre-dipping were associated with changes in the BTSCC. Fore-stripping and post-dipping significantly affected BTSCC. Abstract: The aims of this study were to evaluate the effects of milking method, disinfection practices and other management factors on the bulk tank milk somatic cell count (BTSCC) in tropical dairy herds and to examine potential interactions with time. One hundred and thirty farms in the Northern region of Antioquia, Colombia, were visited once per month for 24 months. A two level linear mixed model for repeated measures was used to assess the impact on log transformed BTSCC (lnBTSCC). The geometric mean of the BTSCC for all herds was 262, 330 cells/mL. The two-level linear mixed model showed that lnBTSCCs in hand milked herds were significantly higher than in machine milked herds. Fore-stripping corresponded with a 27% increase in lnBTSCC and failing to post-dip corresponded with a 45% increase in lnBTSCC. The two way interactions of sampling month with milking method, singeing udders and pre-dipping were significant. The lowest predicted lnBTSCC was observed in machine milked herds that practised both pre-dipping and singeing of udders. This study suggests that milking procedures and disinfection practices can interact with time and have substantial effects on lnBTSCC.